EVALUATION OF THE CARCINOGENIC EFFECTS OF HEAVY METALS ON THE QUALITY OF DRINKING WATER NEAR AIRLINES - Франчук, Г. М.; Маджд, С. М.; Антропченко, А. К. (Science-based technologies, 2014)
Due to the rapid development of air transport is necessary to ensure the environmental safety of land near the airlines. Investigated groundwater directly under carcinogenic from the airport and businesses to repair aircraft. Carcinogenicity - this is a new problem in our society and it requires research and results in all areas of activity. Carcinogenic risk calculations can give an opportunity to evaluate and predict the situation in the environment for future generations. The aim of this research work are: the calculation of the index of groundwater contamination by heavy metals near the airport and evaluation of the carcinogenic risk of contamination of drinking water from wells for the population. To solve this problem was calculated groundwater pollution index, near the airport, and the carcinogenic risk of contamination of drinking water from wells for the population living near the airlines and repair of aircraft. Studies have shown high levels of contamination of groundwater in the area of influence of the airport. Сan be observed with distance from the airport reduces the amount of pollutants and carcinogenic risk for the population.